Bio-inspired assembly of reduced graphene oxide by fibrin fiber to prepare multi-functional conductive bio-nanocomposites as versatile electrochemical platforms. (November 2019) - Zhang, Lin; Liu, Ziyu; Xie, Qingji; Li, Yanbin; Ying, Yibin; Fu, Yingchun
Abstract: Carbon-based bionanocomposites (CBNCs) consisting of 2D carbon nanomaterials and proteins have attracted ever-growing interests in various fields. However, current methods focus on the usage of protein monomers and preformed assemblies as building blocks directly, leaving the dynamic assembly of protein rarely explored though which may bring more flexibility for the fabrication and applications. Inspired by blood coagulation, we propose a novel method to introduce the dynamic formation of fibrin fibers for the assembly of reduced graphene oxide (rGO) to prepare multifunctional fibrin-rGO conductive CBNCs (F-G CBNCs) in a rapid, mild and one-pot way. Benefiting from the unique coagulation-mimicking assembly way and diversified properties of rGO and fibrin fibers, F-G CBNCs are endowed with high conductivity of 26.9 S m -1, as well as good formability, flexibility, mechanical strength, stability, adhesiveness to different surfaces, and electrochemical activity. Moreover, F-G CBNCs show high immobilization ability to enzymes and nanoparticles (load ratios were higher than 94%). Therefore, F-G CBNCs are elaborated as versatile conductive platforms for two modes of electrochemical catalysis and sensing with superior performance. This method may open up a new way to assemble carbon nanomaterials and fabricate high-performance bionanocomposites for diversified applications. Graphical abstract: Image 1